Rubi as a Text: A Note on the Ruby Gloss Encoding - Kazuhiro Okada; Satoru Nakamura; Kiyonori Nagasaki (Journal of the Text Encoding Initiative)
This article describes a proposal for elements of ruby glossing that was incorporated into the TEI Guidelines release 4.2.0, which was codenamed “Ruby.” The Japanese writing system is one of the most complex writing systems in the world, mixing three scripts. The system can also be described as complex in terms of text linearity: the ruby gloss, originally developed from vernacular glosses to Classical Chinese texts, is now a device for presenting a parallel text alongside the main text. Ruby, or rubi, or furigana, can be used to give clues about phonation as well as to present another reading of the text, which sometimes can be an essential part of the text. Such a textual structure requires another layer of semantics besides the existing set of vocabulary, such as , (or ) and . Ruby glosses can also be double-sided. This note discusses the encoding of examples attested in real texts using proposed elements (, , and ), and also considers Taiwanese bopomofo, a related gloss form.